A novel DNA damage repair-related signature for predicting prognositc and treatment response in non-small lung cancer - Li, Ling; Zou, Bao-jia; Zhao, Juan-zhi; Liang, Jia-bi; She, Zi-yue; Zhou, Wen-ying; Lin, Si-xiao; Tian, Lin; Luo, Wen-ji; He, Fa-zhong (Frontiers in Oncology, 2022)
DNA damage repair (DDR) is essential for maintaining genome integrity and modulating cancer risk, progression, and therapeutic response. DDR defects are common among non-small lung cancer (NSCLC), resulting in new challenge and promise for NSCLC treatment. Thus, a thorough understanding of the molecular characteristics of DDR in NSCLC is helpful for NSCLC treatment and management. Here, we systematically analyzed the relationship between DDR alterations and NSCLC prognosis, and successfully established and validated a six-DDR gene prognostic model via LASSO Cox regression analysis based on the expression of prognostic related DDR genes, CDC25C, NEIL3, H2AFX, NBN, XRCC5, RAD1. According to this model, NSCLC patients were classified into high-risk subtype and low-risk subtype, each of which has significant differences between the two subtypes in clinical features, molecular features, immune cell components, gene mutations, DDR pathway activation status and clinical outcomes. The high-risk patients was characterized with worse prognosis, lower proportion and number of DDR mutations, unique immune profile and responsive to immunetherapy. And the low-risk patients tend to have superior survival, while being less responsive to immunotherapy and more sensitive to treatment with DNA-damaging chemotherapy drugs. Overall, this molecular classification based on DDR expression profile enables hierarchical management of patients and personalized clinical treatment, and provides potential therapeutic targets for NSCLC.